Effect of empathy training on the empathy level of healthcare providers in Ethiopia: a cluster randomized controlled trial - Hurissa, Bekana Fekecha; Koricha, Zewdie Birhanu; Dadi, Lelisa Sena (Frontiers in Psychology, 2023)
Objective: Empathy has deteriorated throughout clinical training and medical practice, and little is known about the effect of empathy training on the empathy level of healthcare providers. To address this gap, we assessed the effect of empathy training on the empathy level of healthcare providers in Ethiopia. Design: A Cluster randomized controlled trial study design was conducted from December 20/2021 to March 20/2022. The empathy training intervention was conducted for consecutive three days. Setting: The study was conducted in five fistula treatment centers in Ethiopia. Participants: All randomly selected healthcare providers. Main outcome measures: Total means score, percentage changes, and Cohen’s effect size was computed. A linear mixed effects model and independent t-test were used for data analysis. Results: The majority of study participants were nurses in the profession, married, and first-degree holders. There was no statistically significant difference in the baseline empathy score of the intervention arm across their socio-demographic features. At the baseline, the mean empathy scores of the control and intervention arms were 102.10 ± 15.38 and 101.13 ± 17.67, respectively. The effect of empathy training on the total mean score changes of empathy of the intervention arm compared to the control arm at each follow-up time had a statistically significant difference. After a week, a month, and three months of post-intervention, the total mean empathy scores between the intervention and control arms were: (intervention 112.65 ± 18.99, control 102.85 ± 15.65, d=0.55, P=0.03); (intervention 109.01 ± 17.79, control 100.52 ± 12.57, d=0.53, P=0.034); and (intervention 106.28 ±16.24, control 96.58 ± 14.69, d=0.60, P=0.016) with the overall percentage changes of 11%, 8%, and 5% from the baseline scores, respectively. Conclusions: In this trial, the empathy training intervention was found to have more than a medium effect size. However, over the follow-up intervals, there was a decreasing trend in the total mean empathy scores of healthcare providers; suggesting that there should be continued empathy training and integration of it into educational and training curriculums to enhance the empathy of healthcare providers. Trial registry name: Pan African Clinical Trial Registry; URL: http://www.edctp.org/pan-african-clinical-trials-registry or https://pactr.samrc.ac.za; registration number: PACTR202112564898934